Degradation of malachite green by UV/H2O2 and UV/H2O2/Fe2+ processes: kinetics and mechanism - Wilayat, Sumaira; Fazil, Perveen; Khan, Javed Ali; Zada, Amir; Ali Shah, Muhammad Ishaq; Al-Anazi, Abdulaziz; Shah, Noor S.; Han, Changseok; Ateeq, Muhammad (Frontiers in Chemistry, 2024)
This work investigated the photochemical degradation of malachite green (MG), a cationic triphenylmethane dye used as a coloring agent, fungicide, and antiseptic. UV photolysis was ineffective in the removal of MG as only 12.35% degradation of MG (10 mg/L) was achieved after 60 min of irradiation. In contrast, 100.00% degradation of MG (10 mg/L) was observed after 60 min of irradiation in the presence of 10 mM H2O2 by UV/H2O2 at pH 6.0. Similarly, complete removal (100.00%) of MG was observed at 30 min of the reaction time by UV/H2O2/Fe2+ employing [MG]0 = 10 mg/L, [H2O2]0 = 10 mM, [Fe2+]0 = 2.5 mg/L, and [pH]0 = 3.0. For the UV/H2O2 process, the degradation efficiency was higher at pH 6.0 than at pH 3.0 as the kobs values were 0.0873 and 0.0690 min−1, respectively. However, UV/H2O2/Fe2+ showed higher reactivity at pH 3.0 than at pH 6.0. Chloride and nitrate ions slightly inhibited the removal efficiency of MG by both UV/H2O2 and UV/H2O2/Fe2+ processes. Moreover, three degradation products (DPs) of MG, (i) 4-dimethylamino-benzophenone (DABP), (ii) 4-amino-benzophenone (ABP), and (iii) 4-dimethylamino-phenol (DAP), were identified by GC-MS during the UV/H2O2 treatment. These DPs were found to demonstrate higher aquatic toxicity than the parent MG, suggesting that researchers should focus on the removal of target pollutants as well as their DPs. Nevertheless, the results of this study indicate that both UV/H2O2 and UV/H2O2/Fe2+ processes could be implemented to alleviate the harmful environmental impacts of dye and textile industries.